1997
DOI: 10.1055/s-2007-996075
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Deep Vein Thrombosis with Low-Molecular-Weight Heparins: A Consensus Statement of the Gesellschaft für Thrombose-und Hämostaseforschung (GTH)

Abstract: Recent studies have led to a new concept for the management of deep vein thrombosis. The German Society on Thrombosis and Haemostasis decided to work up the clinical studies in this field published until June 1996 for a consensus statement. The consensus group concluded that (1) high-dose, APTT-controlled subcutaneous administration of unfractionated heparin is as effective as high-dose, APTT-controlled continuous intravenous infusion of unfractionated heparin (grade B recommendation); (2) the anticoagulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…18 Although controversial, special circumstances that may warrant anti-Xa activity monitoring include renal or hepatic insufficiency, extremes of body weight (< 40 kg, > 150 kg), newborns and children, pregnancy, prolonged therapy (> 7-10 days), and the presence of other factors that may increase the risk of bleeding complications such as recent trauma or surgery. 5,10,[22][23][24] Although appropriate timing, frequency, and desired therapeutic range of anti-Xa activity are not clearly defined and remain controversial, peak anti-Xa activity (4 hrs after subcutaneous injection) generally is considered a more useful predictor of LMWH safety and efficacy than trough (just before dose) activity. 18 For prevention of venous thromboembolism (VTE), a peak anti-Xa level of 0.1-0.2 U/ml 4 hours after subcutaneous injection of an LMWH is recommended.…”
Section: Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Although controversial, special circumstances that may warrant anti-Xa activity monitoring include renal or hepatic insufficiency, extremes of body weight (< 40 kg, > 150 kg), newborns and children, pregnancy, prolonged therapy (> 7-10 days), and the presence of other factors that may increase the risk of bleeding complications such as recent trauma or surgery. 5,10,[22][23][24] Although appropriate timing, frequency, and desired therapeutic range of anti-Xa activity are not clearly defined and remain controversial, peak anti-Xa activity (4 hrs after subcutaneous injection) generally is considered a more useful predictor of LMWH safety and efficacy than trough (just before dose) activity. 18 For prevention of venous thromboembolism (VTE), a peak anti-Xa level of 0.1-0.2 U/ml 4 hours after subcutaneous injection of an LMWH is recommended.…”
Section: Monitoringmentioning
confidence: 99%
“…102 Several authors suggested that patients with extremes of body weight, often stated as total body weight below 40 kg or above 150 kg, should have periodic monitoring of anti-Xa activity during prophylactic or therapeutic treatment with LMWHs. 5,18,23,24 Unfortunately, few randomized, controlled trials evaluating the effect of weight, height, body surface area (BSA) or body mass index (BMI) and the occurrence of clinically significant bleeding complications or thrombotic events are found in the literature.…”
Section: Extremes Of Body Weightmentioning
confidence: 99%
“…While it is conceivably true that some (or even many) patients with DVT can be safely treated at home with LMWH, we remain ignorant about which particular patients they are. Last, but not least, the conclusions of Levine and Koopman are not corroborated by pathophysiological principles and are clearly rejected by expert opinion, expressed in consensus reports (Harenberg 1997).…”
Section: Home Treatment Of Patients With Proximal Deep Vein Thrombosimentioning
confidence: 99%
“…Standardtherapie der TVT ist heute die Behandlung mit niedermolekularem Heparin (NMH) in einer körpergewichtsad-aptierten Dosis, je nach Präparat 1-mal oder 2-mal täglich subkutan [15,26,27,39] (⊡ Tabelle [39]. Nach stabilem Erreichen eines therapeutischen INR-Wertes kann Heparin abgesetzt werden.…”
Section: Therapieunclassified